Key Factors to Promote Industry 4.0 Readiness at Indonesian Textile and Clothing Firm - Ferly Norman (Engineering, MAthematics and Computer Science (EMACS) Journal, 2020)
This study discusses whether challenges, barriers, and key factors are the readiness of Indonesian Textile and Clothing (TC) firm in adopting Industry 4.0 (I4.0). The research method is by distributing questionnaires with closed questions to TC employees and owners firm. Respondents were given 15 barriers factors of adoption of I4.0 and gave weight with Likert scale method based on the situation in their company. The survey results were then tested by 2 experts from TC company executives and senior researchers from research institutes. The results of the study show that there are 5 major Barrier Factors with an average value of ≥ 4.0 ("Strongly Agree"): 1. High investments, 2. Lack of digital culture and training, 3. Lack of digital infrastructure, 4. Lack of Government regulation and support, 5. Ineffective Change Management. The key to the company's readiness to adopt I4.0 is not limited to only reducing the five barriers above, but requires two prerequisites so that the company has the financial capacity to invest in I4.0 namely; 1. Enlarge profit margins 2. Form a business ecosystem and innovation. This study is one of the first to find out the barriers of Indonesian TC companies in the implementation of I4.0. From the TOE Framework approach, this study highlights the difficulties in the diffusion of technological innovations resulting from the weak execution of national policies on I4.0 (environmental elements). The results of this study can help TC decision makers and practitioners pave the way for the successful implementation of I4.0.